Analysis the significant risk factors on type 2 diabetes perspective of Bangladesh. Issue 6 (November 2018) - Alam Miah, Md. Badrul; Yousuf, Mohammad Abu
Abstract: Millions of people in Bangladesh and the world have a metabolic disease named diabetes. It is also responsible for occurring different kinds of diseases such as heart attack, kidney disease, blindness and renal failure. Diabetes is a deadly, disabling disease whose risk is increasing at an alarming rate day by day perspective to Bangladesh. The detection process of diabetes is a tedious and multilayered task from some important risk factors. Like other diseases, Type2 diabetes also depends on some factors that are known as risk factors of Type2 diabetes. Risk factors are divided into four categories like Scio-economic condition, Habits, Family History and Hard Diseases etc. in proposed system. Initially 731 diabetes and non-diabetes patient's data have been collected from different diagnostic centers, pre-processed and clustered for identifying relevant and non-relevant data. Significant factors are discovered according to four categories. Next correlation is assessment among significant factors. Finally highly significant factors are discovered whose are directly or indirectly associated with type2 diabetes. Results indicate that Age, Area of Residence, Education Level, Social Status, Family Income, Expense, Tobacco, BMI, Family History, Physical Exercise and Hard Diseases have worst impact on Quality of Life (QoL) among all factors of type2 diabetes respectively.